Novel fabricated germanium-doped optical fibres as high absorbed dose measurement detector for mapping gamma-ray Cesium-137 - Bakar, K. S.A.K.; Noor, N. M.; Idris, F. (Elsevier, 2025)
Measurement of radiation absorbed dose is crucial for assessing potential biological harm to living tissues, ensuring safety and precision in dose delivery to human tissue. TA-GVH disease is a prevalent complication of blood transfusion. The dose mapping method ensures that the radiation dose to the blood remains within the predetermined limits set by authorities up to 50 Gy. This study aims to explore the possibilities of using fabricated germanium-doped (Ge-doped) optical fibre dosimeters as a radiation dose mapper for quality assurance (QA). Two types of fabricated 2.3mol % Ge-doped optical fibres were used, cylindrical (CF) and flat (FF), calibrated within a high dose range of 5–50 Gy using a Cobalt-60 machine at the SSDL, Nuclear Malaysia Agency. Dose mapping was conducted in a Cesium-137 source blood irradiator at the Pathology Department, HSAAS, using blood-equivalent phantom to gamma radiation of 25 Gy and comparing thermoluminescence (TL) signals with EBT-XD film. The result showed no significant difference in mean absorbed dose between both optical fibres and External Beam Therapy (EBT) film. Both fibres exhibited a mean error of 4 %, and EBT-XD film was 3.4 %, indicating good agreement with the nominal dose value of 25 Gy. High radiation exposure can be accurately monitored and assessed using a dosimetry method, such as Ge-doped optical fibre dosimetry. This passive dosimeter offers high sensitivity, cost-effectiveness, and reusability, making it a valuable alternative to conventional blood dosimetry. Comprehensive dose mapping allows for precise monitoring and evaluation of the radiation field, ensuring accurate assessment of radiation exposure in high-dose radiation environments.